BIMBINGAN SOSIAL UNTUK MENGEMBANGKAN PERILAKU ASERTIF REMAJA (Jurusan Bimbingan dan Konseling Islam, 2016)
This research aimed to produce effectiveness of social guidance for developing adolescence assertive behavior. The method of research used quasi-experimental research design with non-equivalent pretest-posttest control group design. The sample in this study were adolescence of Child Social Welfare Institution (LKSA) Nugraha 2015, aged 15-17 years, totaling 28 adolescents (15 adolescencents in the experimental class and 13 adolescencents in control class). Data was collected by assertiveness instrument, arranged on the aspects of thought, feeling, and action. The results showed social guidance effective to develop adolescence assertive behavior, increased of ten indicators of self respect and respect for others, positive thinking, responsible for the opinions expressed, open to change, confidence, self esteem, self-acceptance, listening to others, eye contact, give and receive feedback, indicators were not significant for empathy, open body posture, and participate in the association. Recommendations showed for guidance and counseling study program, child social welfare institution (LKSA) and further research.